IMPLEMENTASI METODE EULER PADA GERAK PEGAS DENGAN MENGGUNAKAN SCILAB - Risda Sucianti Azis; Irwan Ramli (Applied Physics of Cokroaminoto Palopo, 2021)
Vibration is the movement of an object back and forth or oscillations that occur periodically. A construction that has mass and elasticity will basically experience vibration, so it must pay attention to the oscillatory nature of the vibration. Excessive vibration will cause a malfunction in the construction, so a model is needed to determine the vibration characteristics of the construction. One of the vibration phenomena is the movement of the spring. To create a spring motion graph using the Euler method, software such as the scilab application is needed. SCILAB is a software for numerical computing that is open source and can be run on Linux, Windows and MacOS operating systems.